Using multiple languages to support mathematics proficiency in a grade 11 multilingual classroom of second language learners: an action research. - Molefe, Terence Baron (My University, 2009)
This study explores whether and how the deliberate use of multiple languages can support or constrain the development of learners’ mathematics proficiency in a multilingual mathematics classroom. The study is an action research in which I transform my teaching, by exploring a new teaching strategy. In the study, learners’ home languages, in addition to English (LoLT), are used in a planned and proactive manner, where a well-selected high cognitive demand task set in multiple languages is used for teaching and learning. The study is done in a grade 11 multilingual mathematics class, at a school where I teach. Findings of the study indicate that Kilpatrick et al’s (2001) five strands of mathematical proficiency prevail across all lessons, that the use of English by both learners and I dominates, and that utterances are mostly conceptual. It is also shown by the findings of the study that using the learners’ home languages in presentation of the mathematical task, and the nature of the task used, supports the learners in the comprehension of the mathematical task, and encourages them to participate more effectively during lessons.
Keywords: Mathematics proficiency; Multilingual classroom; Multiple languages; Action research; Second language learners